Influence of the NICU on the Acoustic Isolation of a Neonatal Incubator - Puyana-Romero, Virginia; Núñez-Solano, Daniel; Hernández-Molina, Ricardo; Jara-Muñoz, Edgar (Frontiers in Pediatrics, 2020)
The neonatal intensive care unit (NICU) is a very noisy place as compared to the intrauterine environment. To protect the neonate’s health, international guidelines suggest avoiding noise levels above 45 dB in NICUs, but this recommendation is not normally met. The incubator acoustic isolation and the acoustic features of the NICU play important roles in determining the noise measured inside the incubator. In this study, the influence of two types of rooms, one with sound-absorbent covering and the other with reverberant surfaces, on the acoustic isolation of a neonatal incubator was evaluated using three acoustic isolation indexes: the level difference, the apparent sound reduction index, and the standardised level difference. Results show that the acoustic isolation of the incubator is very poor, with a level difference below 11 dBA at all frequencies. At 62.5 Hz, the level difference measured in both rooms exhibits a negative value, indicating that the incubator amplifies the noise coming from the NICU. Isolation of the incubator is poor, and the reverberation time (RT) of the containing room influences RT of the incubator, which is consequently higher when the containing room is reverberant; for example, the incubator RT in the reverberant NICU is 0.72s higher at 500 Hz than that in a room with sound-absorbent covering.